2002
DOI: 10.1046/j.1365-2370.2002.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of HLA class II alleles with pulmonary tuberculosis in Thais

Abstract: Tuberculosis is an important infectious disease in Thailand. Susceptibility to tuberculosis is influenced not only by the environment but also by host genetic factors. In this study, we investigated HLA alleles in 82 patients with tuberculosis from Bangkok and in 160 normal controls. HLA-DRB1, DQA1 and DQB1 genotyping was performed by the PCR-SSO method. The frequency of HLA-DQB1*0502 was increased in tuberculosis patients compared to the normal controls (P = 0.01, OR = 2.06). In contrast, the frequencies of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 12 publications
0
44
2
2
Order By: Relevance
“…The MHC class I and class II gene HLA-DRB1*02, DRB1*1501 North Eastern Indian [77] No particular HLA type confirmed South India [78,79] HLA-DR2 Iranian [80] HLA-DRB1*07, DQA1*0101 HLA-DQA1*0301, *0501 Thais [81] HLA-DQB1*0502 DQA1*0601, DQB1*0301…”
Section: Hivmentioning
confidence: 99%
“…The MHC class I and class II gene HLA-DRB1*02, DRB1*1501 North Eastern Indian [77] No particular HLA type confirmed South India [78,79] HLA-DR2 Iranian [80] HLA-DRB1*07, DQA1*0101 HLA-DQA1*0301, *0501 Thais [81] HLA-DQB1*0502 DQA1*0601, DQB1*0301…”
Section: Hivmentioning
confidence: 99%
“…However, other studies have reported no association. Yuliwulandari found that DRB1*1202 showed a protective effect against TB in Indonesia (Yuliwulandari et al, 2010), whereas Vejbaesya (Vejbaesya et al, 2002) reported no significant difference in DRB1 alleles between TB patients and controls in Thailand. Another report from Brazil showcased overrepresention of DRB1*04 and under-representation of DRB1*15 in TB patients (Lucena et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In Mexican patients with TB a significant positive association with DQB1*0501 was reported by TeranEscandon et al, 5 whereas in a Thai population DQB1* 0502 was found more frequently in subjects with TB. 6 In Cambodia an association was found between TB and DQB1*0503 but not with DQB1*0501 or DQB1*0601. 7 A negative association between the presence of M tuberculosis and DQB1*0301 in Thai subjects and DQB1*0402 in Mexicans was noted.…”
Section: Discussionmentioning
confidence: 85%
“…1 Since the DR alleles play an important role in the modulation of the immune response, a possible association between DQB alleles and TB has been examined in Asian and American ethnic groups, but the results have been inconsistent. [2][3][4][5][6][7] Despite the rising incidence of TB in Europe, no such analysis has yet been carried out in European white populations. A study was therefore undertaken to evaluate the occurrence of DQB1 alleles in TB patients and healthy controls in the same ethnic group in Poland.…”
mentioning
confidence: 99%